A Prospective Study of Pressure Injury Healing Rate and Time and Influencing Factors in an Acute Care Setting. (December 2022) - Seo, YoungMin; Oh, HyunSoo; Na, YoungSun; Kim, MiJin; Seo, WhaSook
ABSTRACT: OBJECTIVE: To determine pressure injury (PI) healing rate and time and identify influencing factors. METHODS: A prospective cohort research design was used. Data collection was performed between May 2015 and August 2018. The study participants were 77 inpatients who developed at least one PI during their stay in a university hospital. Researchers assessed participants' demographic (age, sex); physical (incontinence, activity of daily living, and nutrition status); physiologic (serum total protein, albumin, and creatinine, blood glucose, and hemoglobin levels); and disease- (diagnosis, number of comorbidities, and cardiovascular comorbidity), wound- (PI stage and size at first detection, and Pressure Ulcer Scale for Healing score), and treatment-related (IV nutrition supply and albumin infusion) factors. RESULTS: Across the 77 patients, 91 PIs developed. Of these, 54 (59.3%) healed with a mean healing time of 17.63 days. The healing rate was better, and the healing time was shorter for stage 2 PIs compared with unstageable or deep-tissue PIs. Factors influencing PI healing rate were number of comorbidities, cardiovascular comorbidity, incontinence, PI stage at first detection, IV nutrition supply, and mean serum creatinine level. Factors influencing PI healing time were number of comorbidities, cardiovascular comorbidity, and PI stage at first detection. CONCLUSIONS: To reduce hospital stays, PI-related complications, and mortality, evidence-based management strategies for PIs are needed. The findings of the present study may contribute to the development of such strategies.